Efeitos de uma recordação: quais alterações psicofisiológicas e de autoavaliação ocorrem ao reviver em imagens os Jogos Paralímpicos de 2016? - Soares, Bruna Bardella de Revoredo Macedo [UNIFESP] (2020)
The growth of Paralympic sport has generated increased level of competitiveness leading to higher levels of anxiety and arousal that can impair performance in competitions. One of the models that seeks to explain the relationship between emotional state and performance is The Individual Zones Of Optimal Functioning (IZOF), which considers that athletes have ideal zones of ideal functioning, and one of the ways to understand this zone is remembering past competitions. Based on the IZOF theory, the rescue of emotions and on the understanding of its effects as indispensable factors for high performance Paralympic swimmers to reach and manage their ideal zone, the objective of this study was to use recordings of past competitions as a way to evaluate perception (satisfaction and tension) and the effect of the athlete watching the videos in relation to emotional response (cognitive and physiological arousal) and the self- assessment of their performance. The State-Trait Anxiety Inventory (STAI) was used to obtain cognitive arousal, the Self-Assessment Manikin Scale (SAM) for the athlete to assess the state of tension and perception before and after the swimmers watched the recordings. The video contained three moments: baseline (BL), neutral video (NV) and video of the 2016 Paralympic Games (PGAMES). While watching the recordings, the psychophysiological signs were analyzed, Heart Rate Variability (HRV) and Electrodermal Activity (EDA), as an indicator of physiological arousal, both raw data and percentage changes in relation to BL. Significant differences were observed between the mean time of the heartbeat (MRR) in relation to NVxPGAMES, and a reduction in the parameters RMSSD (square root of the mean of the differences between the intervals) and pNN50 (percentage of RR intervals with a variation greater than 50 milliseconds) although not statistically significant. A reduction in MRR was also observed when the athlete rated his performance as better than expected. Regarding skin conductance, sympathetic activation occurred in VJOGOS when compared to VN. In summary, PGAMES had presented physiological arousal when compared to VN, while the use of video in the psychological and sports fields can be explored, your use should be cautions because can elicit positive or negative responses to performance.